2021
DOI: 10.3390/jcm10204770
|View full text |Cite
|
Sign up to set email alerts
|

The Person’s Care Requires a Sex and Gender Approach

Abstract: There is an urgent need to optimize pharmacology therapy with a consideration of high interindividual variability and economic costs. A sex–gender approach (which considers men, women, and people of diverse gender identities) and the assessment of differences in sex and gender promote global health, avoiding systematic errors that generate results with low validity. Care for people should consider the single individual and his or her past and present life experiences, as well as his or her relationship with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 185 publications
(232 reference statements)
0
10
0
Order By: Relevance
“…Globally, this systematic review attempted at categorizing the abundance of many metabolites to one sex or the other, also considering possible variations related to the age of the analyzed individuals. As demonstrated by the critical selection of only a small number of articles, our work showed that sex is not still adequately considered in metabolomics-based investigations, despite the mounting evidence of its clinical importance for diagnosis, therapy, and outcome [ 83 ]. In particular, the low number of eligible manuscripts that consider the baseline metabolome in healthy individuals, in combination with the high heterogeneity of their data owing to the different metabolomics platforms, statistical approach, and population size, have hindered any process of meta-analysis that was initially planned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, this systematic review attempted at categorizing the abundance of many metabolites to one sex or the other, also considering possible variations related to the age of the analyzed individuals. As demonstrated by the critical selection of only a small number of articles, our work showed that sex is not still adequately considered in metabolomics-based investigations, despite the mounting evidence of its clinical importance for diagnosis, therapy, and outcome [ 83 ]. In particular, the low number of eligible manuscripts that consider the baseline metabolome in healthy individuals, in combination with the high heterogeneity of their data owing to the different metabolomics platforms, statistical approach, and population size, have hindered any process of meta-analysis that was initially planned.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we recognized that sex is not still adequately considered in metabolomics-based investigations. Historically, the female sex has been under-represented in both human and animal experimentations, being considered a confounding variable [ 83 , 100 ]. This outlook can draw misleading evidences that are not equally applicable to both sexes.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Several disparities in diagnosis, therapy, and outcomes have been motivated by the lack of investigations in female animals and women. The rareness of EBM results has created a bias that particularly affects women, who have historically been neglected in clinical research except for studies on the procreative apparatus [11,12]. Regarding the pharmacological responses of human beings, it depends on numerous factors and their reciprocal relationships, and it has been known that sex and gender differences imply drug consumption and adherence to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pharmacological responses of human beings, it depends on numerous factors and their reciprocal relationships, and it has been known that sex and gender differences imply drug consumption and adherence to therapy. Another factor recently investigated is the intestinal microbiota, conditioned by sex-gender differences, able to mitigate drug side effect, affects drug efficacy, and control antibiotic resistance [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In general, women were more likely to report gastrointestinal and nervous systems issues compared with men, which can lead to the higher female hospital frequentation observed in this study. There are several factors that can also influence these differences [ 49 , 50 ], such as the connection between hormones [ 51 ], a different pattern of co-prescribed medications, or other gender issues [ 52 , 53 ] that are nowadays undetected [ 54 ]. What is more, differences between males and women in sexual side-effects highlight the need for introducing this component in analgesic AE monitoring [ 55 ].…”
Section: Discussionmentioning
confidence: 99%